2019
DOI: 10.1136/bmjophth-2018-000194
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterisation of optic nerve and retinal changes in primary congenital glaucoma using hand-held optical coherence tomography

Abstract: ObjectiveTo investigate (1) the feasibility of scanning the optic nerve (ON) and central retina with hand-held optical coherence tomography (HH-OCT) without sedation or anaesthesia in primary congenital glaucoma (PCG), (2) the characteristics of ON changes in comparison with adult primary open-angle glaucoma (POAG) in comparison with matched controls, (3) the sensitivity and specificity of ON parameters for diagnosis, and (4) changes of foveal morphology.Methods and analysisHH-OCT (Envisu 2300; Leica Microsyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Generally, the diagnosis is confirmed based on clinically assessed parameters such as IOP, ONH morphology, changes to the cornea, and, if possible, functional (e.g., perimetric) tests [ 25 ]. The availability and reliability of these parameters often depend on the patient’s cooperation [ 27 ]. Reliable SD-OCT measurements also require the patient’s compliance and can therefore be difficult to obtain from young children.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the diagnosis is confirmed based on clinically assessed parameters such as IOP, ONH morphology, changes to the cornea, and, if possible, functional (e.g., perimetric) tests [ 25 ]. The availability and reliability of these parameters often depend on the patient’s cooperation [ 27 ]. Reliable SD-OCT measurements also require the patient’s compliance and can therefore be difficult to obtain from young children.…”
Section: Discussionmentioning
confidence: 99%
“…Our focus should be especially on cup depth and morphology of lamina cribrosa testing RNFL thinning by SD-OCT in pediatric patients. Some of the included studies elucidated the stage of glaucoma (25,26) and others were not (27)(28)(29)(30)(31)(32)(33), which may influence our metaanalysis of RNFL thickness. These could explain the high degree of statistical heterogeneity between the studies in the metaanalysis.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have reported the thinning of average pRNFL thickness in all sectors between pediatric glaucoma and controls (25)(26)(27)(28)(29)(30). However, other studies have found that children with glaucoma and normal participants have comparable pRNFL thickness in some regions such as the temporal, nasal, and inferior nasal quadrants (31)(32)(33)(34). Thus, the possible association of each sector between pRNFL thickness and childhood glaucoma remains unclear, which justifies the need for more studies on this issue.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the limited cooperativeness of children, no obvious symptoms may be detected at the early stage and examination equipment is mainly designed for adults; missed or delayed diagnosis or misdiagnosis are therefore common ( 15 ). Patients with PCG always have an abnormal structure of the trabecular meshwork (TM) and anterior chamber angle, and they present with an increase of the intraocular pressure and a further extension of sclera, optic nerve and associated structures.…”
Section: Clinical Characteristics Of Pcgmentioning
confidence: 99%